2021
DOI: 10.1093/cid/ciab309
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Repeat BinaxNOW Severe Acute Respiratory Syndrome Coronavirus 2 Antigen Testing in a Community Setting, Wisconsin, November 2020–December 2020

Abstract: Repeating the BinaxNOW antigen test for SARS-CoV-2 by two groups of readers within 30 minutes resulted in high concordance (98.9%) in 2,110 encounters. BinaxNOW test sensitivity was 77.2% (258/334) compared to real-time reverse transcription-polymerase chain reaction. Same day antigen testing did not significantly improve test sensitivity while specificity remained high.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
54
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(56 citation statements)
references
References 6 publications
1
54
1
Order By: Relevance
“…Eighteen studies with 34,865 participants were retrieved [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. Figure 1 depicts the process of the literature search, and Table 1 presents detailed characteristics of the studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eighteen studies with 34,865 participants were retrieved [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. Figure 1 depicts the process of the literature search, and Table 1 presents detailed characteristics of the studies.…”
Section: Resultsmentioning
confidence: 99%
“…All studies in the meta-analysis used a prospective study design, and five studies enrolled participants in the drive-through testing sites [16,19,26,28,31]. Eight studies evaluated the diagnostic performance of antigen tests with nasal swab specimens [16,18,22,23,[28][29][30]33], six assessed the accuracy of antigen tests with nasopharyngeal swab specimens [21,[24][25][26][27]31], seven provided cycle threshold (Ct) values of positive RT-PCR tests [24,25,[28][29][30][31][32], and eight reported cutoff values of Ct [16,[21][22][23]25,27,28,33]. Table 2 lists the statistical data.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to insufficient data, we did not perform subgroup analysis with respect to test type (antigen vs. molecular) and end-user (layperson (self-testing) vs. trained staff/health care worker). Except for 1 study [61,74] where the testing procedure involved (supervised) self-collection of samples by study participants, in all other studies, testing was conducted with trained staff and/or health care workers (if reported). Univariate metaanalysis with random effects for sensitivity and specificity in cases where only a few studies were included (mixed population of symptomatic and asymptomatic children) did not show remarkable differences to the bivariate analysis.…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…CC-BY 4.0 International license It is made available under a is the author/funder, who has granted medRxiv a license to display the preprint in perpetuity. (which was not certified by peer review) 1 1 queries led to the inclusion of 8 further studies [48,50,51,54,61,63,64,67] resulting in a total of 17 relevant studies for this review (12 peer-reviewed journal articles and 5 preprints). The full list of included studies is reported in Table 3.…”
Section: Diagnostic Accuracy Measures and Data Synthesismentioning
confidence: 99%